The Illusion and Reality: A Distressing Exploration of American Dream of Success - Priyank Sonwani; Dr Ravi Kumar Yadav (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
F. Scott Fitzgerald's body of work is a profound and poignant exploration of the illusion and reality of success. His characters are relentlessly driven by the American Dream, believing that wealth, social status, and material possessions will lead to happiness and fulfilment. However, through their tragic journeys, Fitzgerald reveals that this pursuit is a hollow one. The reality of success in his novels is not a glittering triumph but a moral and spiritual bankruptcy, a testament to the idea that the "dream" is a deceptive mirage that corrupts the very souls it promises to save.
Keywords: American Dream; Identity; Illusion; Realism; Existentialism